Spring notes of birds sighted by Thomas H. Kent, March 1 to May 14, 1978 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1978)
Field report titled "spring notes of birds sighted by Thomas H. Kent, March 1 to May 14, 1978." This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring, 1978. Epson - sheet feed/flatbed